ANALISIS PUPUK ORGANIK LIMBAH CAIR KELAPA SAWIT (LCKS) DI DESA AIR MERAH KECAMATAN KAMPUNG RAKYAT - Fazri, Muhammad; Rizal, Khairul; Sepriani, Yusmaidar; Zamzami, Lutfi Fadilah (Agros Journal of Agriculture Science, 2024)
Liquid Palm Oil Waste (LCKS) is waste produced from the palm oil processing process, which can be processed into liquid organic fertilizer through fermentation and the addition of microbes. This research aims to analyze the nutrient content contained in liquid palm oil waste fertilizer. This research was carried out from January to April. The research method used is a direct survey method in the field to carry out the process of making organic fertilizer from liquid palm oil waste. The research results show that this fertilizer has an organic C content of 48.38%, pH 4.37, nitrogen (N) 2.20%, phosphorus (P) 0.39%, and potassium (K) 1.41%. The production process involves fermentation with the addition of microbes to improve the quality of the fertilizer. The research results show that the high C-organic content, appropriate pH value, and nitrogen content that meets quality standards make this fertilizer effective for plant growth. Even though the phosphorus and potassium levels are below quality standards, LCKS organic fertilizer still contains important nutrients and essential microelements that support soil fertility and plant productivity.Key-words: Palm oil liquid waste, organic fertilizer, POC, nutrients